Social inequalities in pure-tone hearing assessed using occupational stratification schemes. - von Gablenz, Petra; Holube, Inga (International Journal of Audiology, 2017)
Objective: The objective of this study is to analyse the performance of two occupational stratification approaches and the impact of social position on adult hearing.Design: The prevalence of hearing impairment, pure-tone averages (PTA) and prevalence ratios (PR) for relative hearing loss, which focuses on the position of one’s PTA in the age- and gender-specific distribution, were compared in groups defined by ISCO Skill Level and the International Socio-Economic Index (ISEI).Study sample: About 1571 subjects aged 30–89, including 677 highly screened adults, from the cross-sectional study HÖRSTAT.Results: ISCO Skill Level and ISEI yielded qualitatively the same results. The prevalence difference between the socially least and most advantaged group ranges between 10 and 16%, varying with the scheme applied. Low- and high-frequency PTA and PR for relative hearing loss confirm the gradient. Screening reduced, but did not negate the social differences. The prevalence difference dropped to 6–7% in the otologically normal subsample.Conclusions: Social groups defined by hierarchical, occupational measures differ in their pure-tone hearing, even if the main risk factors are controlled for. This underlines the need for population-based sampling, the relevance of reporting the study group’s social composition and the importance of advancing the discussion on appropriate social measures in hearing research.